Limitations on the Use of Artificial Intelligence in Presidential and Vice-Presidential Election Campaigns - Azizah, Amatulloh; Wardhana, Allan Fatchan Gani (Fakultas Hukum Universitas Hang Tuah, 2026)
With the advancement of digital technology, AI has been increasingly used in political campaign. This study examines the urgency of limiting the use of AI in presidential and vice-presidential election campaigns and analyzes the legal implications of Constitutional Court Decision Number 166/PUU-XXI/2023 on the use of AI in in Presidential and Vice-Presidential Election Campaign. Using a normative legal research method with statutory and case approaches, this study finds that excessive AI-based image manipulation undermines voters’ rights to accurate information and threatens free and fair elections. The decision requires lawmakers to revise election regulations, obliges election participants to avoid excessive AI use, strengthens voters’ access to truthful information, and mandates election management bodies to enhance oversight. This study contributes to election law and digital governance by reinforcing democratic integrity in the digital era.